Radiocarpal and Midcarpal Instability in Rheumatoid Patients: A Systematic Review - Raven, Eric E.J. (Open Orthop J, 2015)
BACKGROUND: This study was aimed at identifying the criteria for the diagnosis of Radiocarpal instability in rheumatoid arthritis RA). METHODS: The main databases were searched to identify studies describing the pathophysiology of Radiocarpal instability in patients with RA. We focussed on the epidemiology, radiographic parameters, criteria for instability and on treatment options. Results. In the search 108 articles were found, of these 12 studies were included for this review. Instability occurs in at an average of 35.2% of the rheumatoid wrists. The instability was found between 8 and 13 years after onset of rheumatoid arthritis. A strong correlation was found between instability, duration of RA and Larsen score. Several radiographic methods were described to evaluate Radiocarpal instability in RA. Several treatment options for instability in patients with RA are described. All with their own indications and limitations. CONCLUSION: On a standard AP radiograph deformity can be measured using the carpal height and the ulnar translation index of Chamay. This gives an indication for instability. For describing the deterioration of the joints the Larsen score is most used. If there are more radiographs in time the Simmen classification can be used. For real assessment of instability dynamic radiographs are needed. LEVEL OF EVIDENCE: Level IV.